2017
DOI: 10.1186/s13256-016-1180-4
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of synchronous recurrent breast carcinoma with chronic myelogenous leukemia: a case report

Abstract: BackgroundSurvival is increasing after early breast cancer revealing frequent relapses and possibility of developing secondary malignancies. The concomitant occurrence of these two events is exceptionally disastrous and lethal. We report a case of a Moroccan woman who was successfully managed for synchronous recurrent breast carcinoma and chronic myelogenous leukemia.Case presentationA 42-year-old Moroccan woman was diagnosed with localized breast carcinoma in 2008. She received six cycles of an adjuvant chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Secondary primary malignancy of the breast, neuroendocrine tumor of the caecum, squamous cell carcinoma of the skin, acute lymphocytic leukemia have been reported but there has been no case of any benign tumor being reported in the literature [9][10][11]. Elmhadi et al reported a case of successful management of synchronous recurrent breast carcinoma with chronic myelogenous leukemia [12]. Pan L et al reported a case of secondary breast carcinoma after completely remitted chronic myeloid leukemia following targeted tyrosine kinase therapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary primary malignancy of the breast, neuroendocrine tumor of the caecum, squamous cell carcinoma of the skin, acute lymphocytic leukemia have been reported but there has been no case of any benign tumor being reported in the literature [9][10][11]. Elmhadi et al reported a case of successful management of synchronous recurrent breast carcinoma with chronic myelogenous leukemia [12]. Pan L et al reported a case of secondary breast carcinoma after completely remitted chronic myeloid leukemia following targeted tyrosine kinase therapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…The results of randomized clinical trials have suggested that patients with primary breast carcinoma have an increased risk of developing leukemia. But this risk is not well characterized [7,8,9]. Increase in risk is attributable to adjuvant therapy, especially anthracycline and alkylating agent dose intensification, and perhaps to concomitant radiotherapy use.…”
Section: Discussionmentioning
confidence: 99%